"We Need Community": Assessing the Impact of Faculty, Advising, Campus Social Life, and Racial Formation on the Transfer Student Experience at a Diverse Island Campus. (September 2019) - Hern, Lindy; McKay, Remi; Brown, Susan
In this paper, we examine the experiences of lower division transfer students at a diverse island campus. We conducted this study to increase our understanding of why lower division transfer students are one of the most at-risk populations in relation to completing their education at Island University. The question "how might the institution better serve these students in order to increase retention" guided our research process. The intended goal was practical—to create new programming that facilitated the process of transferring to Island University and increased student retention—specifically in relation to lower division transfer students. The conclusions drawn from the data also have important implications for a more general understanding of the problem of creating socially just educational systems, which is highlighted by the issue of student retention—especially on diverse campuses that serve economically disadvantaged communities.